1994
DOI: 10.1006/cbir.1994.1104
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maternal nicotine exposure on the interalveolar septal status of neonatal rat lung.

Abstract: The aim of this study was to determine the effect of maternal nicotine exposure (1 mg nicotine/kg body mass/day, subcutaneously) on the status of the alveolar septa of the 1 to 21 day old offspring. The data obtained showed swelling of type II and interstitial cell mitochondria. The type I:type II cell ratio decreased as a result of type II cell proliferation. The number of capillaries per unit length of septum was also significantly lower than that of control lung. Ruptured blood-air barriers also occur in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…Collins et al (8) exposed pregnant rats to cigarette smoke and similarly found enlarged and fewer saccules in fetal rats after cigarette smoke exposure. Maritz et al (9,42) treated rats with a combination of pre-and postnatal nicotine and similarly found decreased radial alveolar count and increased mean linear intercept in neonatal rats. The finding that nicotine alters alveolar development in both monkeys and rodents makes it highly likely that prenatal exposure to nicotine will similarly affect human lung development.…”
Section: Discussionmentioning
confidence: 96%
“…Collins et al (8) exposed pregnant rats to cigarette smoke and similarly found enlarged and fewer saccules in fetal rats after cigarette smoke exposure. Maritz et al (9,42) treated rats with a combination of pre-and postnatal nicotine and similarly found decreased radial alveolar count and increased mean linear intercept in neonatal rats. The finding that nicotine alters alveolar development in both monkeys and rodents makes it highly likely that prenatal exposure to nicotine will similarly affect human lung development.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that nicotine treatment not only causes swelling and structural remodeling of mitochondria in cells of various tissues, including the brain (Jin and Roomans 1997; Maritz and Thomas 1994; Onal et al 2004; Zimmerman and McGeachie 1987), but also regulates processes such as protein turnover (Katyare and Shallom 1988), enzyme activity (Barbieri et al 1989; Galvin et al 1988), and generation of ROS (Bhagwat et al 1998; Soto-Otero et al 2002). Here, we further demonstrate that the genes of each complex in the electron transfer system are modulated by chronic nicotine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the proliferation of the alveolar type II cells, the type I/type II cell ratio decreased in the lungs of these animals (Maritz and Thomas, 1994). Nicotine also stimulates surfactant synthesis in type II cells (Maritz and Thomas, 1994;Rehan et al, 2007).…”
Section: Structural Developmentmentioning
confidence: 95%
“…As a consequence of the proliferation of the alveolar type II cells, the type I/type II cell ratio decreased in the lungs of these animals (Maritz and Thomas, 1994). Nicotine also stimulates surfactant synthesis in type II cells (Maritz and Thomas, 1994;Rehan et al, 2007). Pulmonary fibroblasts are thought to be positive modulators of this process through the synthesis of keratinocyte and hepatocyte growth factors, both known to be potent mitogens for type II cells (Panos et al, 1993).…”
Section: Structural Developmentmentioning
confidence: 95%
See 1 more Smart Citation